Discovery of ecnoglutide - A novel, long-acting, cAMP-biased glucagon-like peptide-1 (GLP-1) analog - Wanjun Guo; Zheng Xu; Haixia Zou; Feng Li; Yao Li; Jing Feng; Zhiyi Zhu; Qing Zheng; Rui Zhu; Bin Wang; Yan Li; Sujuan Hao; et al. (Elsevier, 2023)
Objective: Glucagon-like peptide (GLP)-1 is an incretin hormone that acts after food intake to stimulate insulin production, enhance satiety, and promote weight loss. Here we describe the discovery and characterization of ecnoglutide (XW003), a novel GLP-1 analog. Methods: We engineered a series of GLP-1 peptide analogs with an alanine to valine substitution (Ala8Val) and a γGlu-2xAEEA linked C18 diacid fatty acid at various positions. Ecnoglutide was selected and characterized in GLP-1 receptor signaling assays in vitro, as well as in db/db mice and a diet induced obese (DIO) rat model. A Phase 1, double-blind, randomized, placebo-controlled, single (SAD) and multiple ascending dose (MAD) study was conducted to evaluate the safety, tolerability, and pharmacokinetics of subcutaneous ecnoglutide injection in healthy participants. SAD doses ranged from 0.03 to 1.0 mg; MAD doses ranged from 0.2 to 0.6 mg once weekly for 6 weeks (ClinicalTrials.gov Identifier: NCT04389775). Results: In vitro, ecnoglutide potently induced cAMP (EC50 = 0.018 nM) but not GLP-1 receptor internalization (EC50 > 10 μM), suggesting a desirable signaling bias. In rodent models, ecnoglutide significantly reduced blood glucose, promoted insulin induction, and led to more pronounced body weight reduction compared to semaglutide. In a Phase 1 trial, ecnoglutide was generally safe and well tolerated as a once-weekly injection for up to 6 weeks. Adverse events included decreased appetite, nausea, and headache. The half-life at steady state ranged from 124 to 138 h, supporting once-weekly dosing. Conclusions: Ecnoglutide showed a favorable potency, pharmacokinetic, and tolerability profile, as well as a simplified manufacturing process. These results support the continued development of ecnoglutide for the treatment of type 2 diabetes and obesity.